Magnetic treatment recirculation agricultural wastewater system - Nor Hidayah Othman (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
This study of magnetic treatment recirculation agricultural wastewater is conducted using a permanent magnet. The treatment process is run for five day where one day of treatment process is equal to 8 hours. Besides that, the constant flow rate and magnetic strength is used that 25 L/min and 1.32 Tesla. This treatment process is repeated for two times to indentify the performance of magnetic treatment. The performance of the system determined by suspended solid, nutrient (ammonia, Nitrate and phosphate), Chemical Oxygen Demand (COD) and pH value of wastewater before and after the treatment process. The result shows great removal efficiency for suspended solid, Phosphorus, nitrate and chemical oxygen demand. This study concludes magnetic treatment recirculation systems can treat the agricultural wastewater.